Sistem Informasi Pelaporan Pekerjaan Proyek Berbasis SDLC Modelling (Studi Kasus: PT Vertikal Tiara Manunggal) - Eric Alfonsius; Sukardi Sukardi; I Made Nopa Vendi Astawa (Journal of Artificial Intelligence and Technology Information (JAITI), 2023)
The research presented in this article examines the process of developing a corporate reporting website that can provide comprehensive information about the firm so that anyone looking for information can learn everything there is to know about the business. To make it simpler for users to acquire information about Tiara Manunggal Vertical Company, this research will build a website as an alternative communication channel. Information is gathered using the techniques of observation, documentation, and interviews to help the website building process. Using the BlackBox testing procedure, the results of this research were put to the test. The results of system functionality testing using blackbox testing show that all functions run properly and validly, with a percentage level of 100% in accordance with the functions of the application created.